Kierunki zmian sektora bankowego - Wójcik, Sławomir (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The dissertation is an attempt to present trends in contemporary banking after the latest global economic downturn. An opinion of being reliable and responsible among esteemed institutions is what banks from all over the world have to compete for. The implementation of the customer service based on rectitude and high ethical standards, provision of the full banking products’ information and last but not least, individual approach to customers’ needs and expectations are steps on the path leading to this goal. Moreover, some changes connected with canvass have been noted. The introduction of original marketing strategies intended to create modern and at the same time customer-friendly image of these institutions introduction, demands attention. Besides banks enter new fields of activity. The main purpose of all mentioned moves is to build long–lasting client–bank relations — the basis of banks’ presence on the market.
Keywords: bank; sektor bankowy; zmiany